Pillowland - Berkner Laurie (New York; Simon & Schuster Books for Young Readers, 2017)
Laurie Berkner's treasured song "Pillowland" is now a beautiful picture book! Featuring magical, lush art by Camille Garoche, Pillowland carries readers away to a feather-fluffed dream world where bedtime is always a grand adventure
Keywords: Picture books for children